PENGARUH PEMBANGUNAN INFRASTRUKTUR TERHADAP PERKEMBANGAN UMKM DAN PARIWISATA DI KABUPATEN BERAU: PENGARUH PEMBANGUNAN INFRASTRUKTUR TERHADAP PERKEMBANGAN UMKM DAN PARIWISATA DI KABUPATEN BERAU - Ardianti Maya Ningrum (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
The research aims to investigate the impact of infrastructure development on the growth of Micro, Small, and Medium Enterprises (UMKM) and Tourism in Berau Regency. Based on the analysis of the data and discussion presented, it is concluded that infrastructure development has an influence on the growth of UMKM in Berau Regency. The addition and improvement of roads, bridges, and public facilities have fostered UMKM growth in trade, industry, and services sectors. Infrastructure development also affects tourism in Berau Regency. Improvements in road access and the airport have increased the number of tourist visits to Berau Regency throughout the years 2021-2022.